SPE Asia Pacific Oil and Gas Conference and Exhibition 2004
DOI: 10.2118/88630-ms
|View full text |Cite
|
Sign up to set email alerts
|

Indonesia: Coalbed Methane Indicators and Basin Evaluation

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractIndonesia has thick, low-rank coal deposits that are prospective for coalbed methane (CBM) development but remain untested. Conventional oil and gas wells that drill through these coal seams experience gas kicks and blow outs, good CBM indicators. We analyzed petroleum and coal mining data to perform a comprehensive assessment of Indonesia's CBM resources. We identified 12.7 trillion m 3 (450 Tcf) of prospective CBM resources within eleven onshore coal basins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 1 publication
2
25
0
2
Order By: Relevance
“…The correlation of seams on logs implies that lateral continuity of strata is extensive. This interpretation is concordant with that proposed by [13] and [19]. Results of log observation show that there appear at least four major coal beds, known as A1, A2, B, and C seams (Fig.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The correlation of seams on logs implies that lateral continuity of strata is extensive. This interpretation is concordant with that proposed by [13] and [19]. Results of log observation show that there appear at least four major coal beds, known as A1, A2, B, and C seams (Fig.…”
Section: Resultssupporting
confidence: 91%
“…More importantly, the deep coal seams in the islands are apparently to be the key reservoir system that currently becomes the main target for CBM exploration. Based on volumetric calculation, the South and Central Sumatra basins are inferred to have CBM prospectivity of approximately 183 tcf and 145 tcf respectively [13]. Besides, these authors reported that the Barito coal seams hold natural gas of about 120 tcf, and the Kutei basin comprises gas potential of around 51 tcf.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Tcf of CBM resources (Stevens and Hadiyanto, 2004). The coal in the SSB ranges from in depth 300-1000 m and is mostly sub bituminous (Rv 0.4-0.5%) in rank with high vitrinite contents (> 90%) and extremely low ash yields (< 5%).…”
Section: Indonesian Cbmmentioning
confidence: 99%
“…The estimated Indonesia's CBM gas in-place is over 450 Tcf. This year is estimated to produce 2.5 mmscfd which will be converted to 6.25 MW electricity (ESDM, 2012;Stevens, 2004).…”
Section: Introductionmentioning
confidence: 99%